Impact of clinical and functional conditions on quality of life in old women with obesity - Marília Caixeta De Araujo; João Marcos Domingues Dias; Karina Simone de Souza Vasconcelos; Adriana Pedrita Pessoa Medeiros; Carla Moura Santos; Rosângela Correa Dias (Universidade de São Paulo, 2014)
Obesity is associated with functional disabilities and impairments of quality of life, and many factors affect this relationship. This study aimed at characterizing and identifying the impact of clinical and functional conditions on health-related quality of life (HRQoL) in obese old women. The HRQoL was assessed by the questionnaires "Outcomes Study Short Form-36 Health Survey" (SF-36) and "Impact of Weight on Quality of Life - Lite" (IWQOL - Lite), which were applied to 63 women with body mass index ≥30 kg/m2. Regression models were developed for general (SF-36) and specific (IWQOL-Lite) HRQoL. The associated factors investigated were: age, number of medicines, number of diseases, depressive symptoms, body mass index, grip strength, level of physical activity, and functional performance. The old women had a low level of strength and physical activity. Their functional performance was good to moderate, but a third of the sample presented deficit of mobility. The level of physical activity and functional performance had a positive impact on the general HRQoL and number of drugs had a negative one (R2=0.44). Depressive symptoms and body mass index negatively affected the specific HRQoL (R2=0.57). The study concluded that obese old women with depressive symptoms, low levels of physical activity, and functional performance, making use of a great number of drugs, are more vulnerable to experiencing poor HRQoL. All the factors associated with the HRQoL in this study are potentially modifiable with interventions of health prevention and promotion.